Sustainable Development of Tagalag Fishing Village as Ecotourism Zone of Valenzuela City, Philippines - Clemente, Paul Timothy; Santo, Riza Delos; Donato, Mary Ann; Lago, Elpedia (Media Konservasi, 2024)
Tagalag, an urban barangay in Valenzuela, has been providing fish supplies to its city since the 1980s. The barangay was established after a massive flood, and in 2016, it was declared a city eco-tourism zone. The Sustainable Development Goals (SDGs) prioritize economic growth, social inclusion, and sustainable development, encompassing objectives pertaining to the tourism sector. The application of the Sustainable Development Goals (SDGs) to the tourism sector has been undertaken by the World Tourism Organization (UNWTO), with the aim of advocating for the implementation of sustainable, equitable, and environmentally friendly practices within the tourism industry. Sustainable tourism encompasses the comprehensive evaluation of its societal, ecological, and economic consequences while simultaneously addressing the requirements of both tourists and local communities, safeguarding natural resources, and mitigating adverse environmental effects. Under the SDG #6 Clean Water and Sanitation this goal is making sure about the Tagalag fishing village has an availability of clean water and good sanitation by all and how this can be sustained in the Tagalag community which the researchers do some recommended plan for the community Tagalag Fishing Village is dedicated to sustainable fishing practices and marine life habitat restoration, implementing scientifically based management programs and regulatory agencies. The village prioritizes water resource conservation and surface runoff reduction but could benefit from enhancing infrastructure and promoting sustainable development. The village's economic growth is exemplary, with policies promoting economic growth, job opportunities, entrepreneurial endeavors, and indigenous culture preservation. However, there is room for improvement in sanitation and clean water.